Integrated and Inclusive Higher Education in Vladimir State University: Current State and Development Perspectives - Yegorov I.N; Panfilov A.N (Moscow State University of Psychology and Education, 2017)
The paper summarizes the many years of experience in methodological support and training at the Center of Professional Education for the Disabled and at the "Inclusive Education" Research and Educational Center of the Vladimir State University. At these centers the work is aimed at establishing a system of continuous higher inclusive education for persons with hearing and visual impairments. The paper focuses on the issues concerning the organization of educational process and the adaptation of learning materials for students with hearing and visual impairments; it addresses the problem of creating a system of academic support for students with disabilities and providing psychological and educational assistance to individuals with hearing and visual impairments in the system of higher education.